Incremental value of left atrial strain to predict atrial fibrillation recurrence after cryoballoon ablation - Andreea Motoc (Public Library of Science (PLoS), 2021)
Objective Atrial fibrillation (AF) recurrence occurs in approximately 25% of the patients undergoing cryoballoon ablation (CBA), leading to repeated ablations and complications. Left atrial (LA) dilation has been proposed as a predictor of AF recurrence. However, LA strain is a surrogate marker of LA mechanical dysfunction, which might appear before the enlargement of the LA. The purpose of this study was to evaluate the additional predictive value of LA function assessed using strain echocardiography for AF recurrence after CBA. Methods 172 consecutive patients (62.2 ± 12.2 years, 61% male) were prospectively analyzed. Echocardiography was performed before CBA. Blanking period was defined as the first three months post-ablation. The primary endpoint was AF recurrence after the blanking period. Results 50 (29%) patients had AF recurrence. In the overall study population, peak atrial longitudinal strain (PALS) ≤ 17% had the highest incremental predictive value for AF recurrence (HR = 9.45, 95%CI: 3.17–28.13, p < 0.001). In patients with non-dilated LA, PALS≤17% remained an independent predictor of AF recurrence (HR = 5.39, 95%CI: 1.66–17.52, p = 0.005). Conclusions This study showed that LA function assessed by PALS provided an additional predictive value for AF recurrence after CBA, over LA enlargement. In patients with non—dilated LA, PALS also predicted AF recurrence. These findings emphasize the added value of LA strain, suggesting that it should be implemented in the systematic evaluation of AF patients before CBA.